ALTERNATIF MEDIA DAN METODE PEMBELAJARAN BAHASA ARAB UNTUK SISWA MADRASAH IBTIDAIYYAH PADA MASA PANDEMI COVID-19 - Fathi Hidayah; Hikmah Nur Laili; Miftahul Unum (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
Learning Arabic for Madrasah Ibtidaiyyah students during the Covid-19 pandemic needs attention. The selection of various media and learning methods is certainly needed. This study aims to describe the application of interactive multimedia and the Mimicry Memorization method in learning Arabic at Madrasah Ibtidaiyyah. This study uses a qualitative research design by taking research subjects at MI Islamiyah, MI Diponegoro, MI Bustanul Ulum and MI AL Amin. Data collection techniques used are observation, interviews and documentation. The data analysis technique used is the qualitative data analysis technique of Miles and Huberman. The results of this study are learning Arabic interactive multimedia for grade 3 students of Madrasah Ibtidaiyyah based on powerpoint with Ar Riyadhah subject. Media content includes; text, audio, video, animation and interactive. The application of the Mimicry Memorization method is divided into 3 stages, the opening activity, the core activity by modifying the introduction of mufrodat using video and closing activities.